A coupled optical-electrical-thermal model of the bifacial photovoltaic module. (15th January 2020) - Gu, Wenbo; Ma, Tao; Li, Meng; Shen, Lu; Zhang, Yijie
Graphical abstract: Highlights: A novel coupled optical-electrical-thermal model of the bifacial PV module is developed. Global irradiances of the front and rear sides are calculated by view factor and irradiance model. Over 22% of the average bifacial gain can be achieved via yearly performance estimation. Suggestions for optimizing the bifacial PV module performance are proposed. Abstract: The bifacial photovoltaic (PV) technology has become prevalent in the global market in recent years as it can simultaneously collect the sunlight from both front and rear sides to achieve high power generation, however, there is limited attention from academic circle on this new technology particularly theory study in multiphysics simulation. This paper develops a comprehensive optical-electrical-thermal model for the bifacial PV module, in which the global irradiances of the tilted front and rear surfaces are obtained through the optical model, the cell temperature through the thermal model, and the power output through the electrical model accordingly. After validation, the coupled model is employed to conduct daily and yearly performance estimations, demonstrating 25.58% and 28.21% of the daily bifacial gain for sunny and cloudy days, respectively, and more than 22% of the yearly bifacial gain for Hong Kong and Shanghai. Besides, it is found that the bifacial gain under low irradiance is relatively high due to high diffuse fraction, indicating that bifacial modules have an advantage in adapting to various weather conditions, especially cloudy days. Furthermore, some suggestions are proposed to optimize the bifacial module by considering the effects of various installation and weather parameters on the PV generation. A tracking bifacial module, installed at an optimum tilt angle with high albedo, elevation, irradiance and wind velocity, but low ambient temperature, could achieve high energy yield, while a bifacial module facing east with high albedo, tilt angle, elevation, diffuse fraction, ambient temperature and wind velocity could achieve high bifacial gain.